Role of Panchatikta Ghrita, Haridra and Nimba Churna Puran in Vrana with Respect to Bed Sore. - Mishra, Reena Shivasgar; chandurkar, Vivek (International Research Journal of Ayurveda & Yoga, 2023)
The Vrana means Damage or destruction of the part or tissue of body, which leaves a scar after healing. From the beginning of civilization, Vrana was one of the major disease which was managed by human being. In ancient Indian literature there was large number of references related to the vrana (wound) and vrana ropan (wound healing) was mentioned. The acharya categorised vrana in to mainly two parts i.e. Nija and Aagantuja vrana along with this many classification, Nidan, Samprapti, Rupa, Lakshanas, vrana pareeksha, and treatment methods for vrana was mentioned in ayurvedic treaties. The healing process of Vrana is a natural process, which also starts immediate after injury. Acharya Sushruta described Vrana at different places in different context of Sushrut Samhita. The vrana is important topic in academic point of view, patient care and research of newer technique and drugs for easier and effective management. The management of wound is described in Sushruta samhita in very detail manner. He advised sixty upakrama (method) of treating wound is lot of different conditions known as shashtiupakram in Chikitsasthanam In this review article we have try to describe and compile the all detail description of vrana and try to compare the vrana ropan procedure with wound healing with the base of Lakshanas of vrana.